2008
DOI: 10.1016/j.jmb.2007.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Characterization of a Novel Family of Cystathionine β-Synthase Domain Proteins Fused to a Zn Ribbon-Like Domain

Abstract: We have identified a novel family of proteins, in which the N-terminal Cystathionine Beta-Synthase (CBS) domain is fused to the C-terminal Zn ribbon domain. Four proteins were over-expressed in E. coli and purified: TA0289 from Thermoplasma acidophilum, TV1335 from Thermoplasma vulcanum, PF1953 from Pyrococcus furiosus, and PH0267 from Pyrococcus horikoshii. The purified proteins had red/purple color in solution and an absorption spectrum typical of rubredoxins. Metal analysis of purified proteins revealed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 75 publications
3
53
0
Order By: Relevance
“…The cloning of the genes encoding PA3455, SMc02148, and other PPK2 proteins (PAPTO1640, PA2428, SMa0172, SMa0670, Atu0418, and RPA4569) into the modified pET15b was carried out as described (23). The proteins were expressed as a fusion with an N-terminal His6 tag in the E. coli strain BL21 (DE3) and purified as described (23,24). Seleno-methionine (SeMet)-labeled proteins were produced by overexpression in the E. coli methionine auxotroph strain B834 (DE3) (Novagen).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cloning of the genes encoding PA3455, SMc02148, and other PPK2 proteins (PAPTO1640, PA2428, SMa0172, SMa0670, Atu0418, and RPA4569) into the modified pET15b was carried out as described (23). The proteins were expressed as a fusion with an N-terminal His6 tag in the E. coli strain BL21 (DE3) and purified as described (23,24). Seleno-methionine (SeMet)-labeled proteins were produced by overexpression in the E. coli methionine auxotroph strain B834 (DE3) (Novagen).…”
Section: Resultsmentioning
confidence: 99%
“…Seleno-methionine (SeMet)-labeled proteins were produced by overexpression in the E. coli methionine auxotroph strain B834 (DE3) (Novagen). Alanine replacement mutagenesis of PA3455 and SMc02148 was performed as described (24).…”
Section: Resultsmentioning
confidence: 99%
“…The proteins were expressed as a fusion with an N-terminal His 6 tag in Escherichia coli strain BL21 (DE3) and purified to more than 95% homogeneity using metal-chelate affinity chromatography on nickel affinity resin and gel filtration on a Superdex 200 26/60 column (Amersham Biosciences) as described before (20,21). Site-directed mutagenesis of SSO1404 was performed as described previously (21) using a protocol based on the QuikChange site-directed mutagenesis kit (Stratagene).…”
Section: Methodsmentioning
confidence: 99%
“…Most of the CBS domains are found as tandem repeats but data base searches have also revealed tetra-repeat units (5). The crystal structures of several tandem CBS domains have been elucidated (7)(8)(9)32), and in a number of cases it has been shown that two tandem CBS domains form dimeric structures with a total of four CBS domains per structural module (hereafter referred to as CBS module). The crystal structures of the full-length MgtE Mg 2ϩ transporter confirm the dimeric configuration and show that the CBS domains undergo large conformational changes upon Mg 2ϩ binding or release (10, 11).…”
mentioning
confidence: 99%